IDENTIFICATION AND DEVELOPMENT OF INTELLECTUAL ASSETS OF INNOVATIVE BUSINESS - STASOVSKA, Galyna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a research review and substantiation of the criteria for identifying intellectual assets of innovative entrepreneurship. The characteristics of the criteria for identifying intellectual assets of innovative entrepreneurship are considered. The study pays attention to the overview of the properties of innovativeness, identification, controllability, economy and digital transformation of business. Innovativeness identifies ideas, knowledge, data, inventions and achievements of unique innovative effects and is implemented as a criterion for the formation of intellectual assets. The "identification" criterion recognizes the intellectual assets of innovative entrepreneurship as a result of scientific and technical renewal and innovative activity. The controllability of intellectual assets is distinguished in the system of managing the development of innovative business and is determined by the organization of control. Cost-effectiveness is determined by the effective use of intellectual assets of innovative business and is evaluated by profit and efficiency. Determining the content of intellectual assets according to the criterion of digital transformation allows you to learn about the strengths of innovative business development in the digital economy. The result of the research is recommended for further scientific developments when making management decisions in the innovative economy. The conclusion of the research is the identification criteria of intellectual assets of innovative entrepreneurship, which determine the principles of their formation in the conditions of the global market. With the development of scientific and technical progress, new challenges arise related to the protection of human rights and freedoms in the digital economy. Digital rights and freedoms of innovative business are reflected in Ukrainian legislation and protection mechanisms; are considered an indispensable condition of innovative business, which requires protection under the conditions of the development of digital technologies. Ukrainian law has been adapted to digital business and regulations have been introduced to improve security mechanisms. Innovative business and partners cooperate to comply with the principles of transparency in the digital space and the protection of digital rights. The conclusions propose digital assets of innovative entrepreneurship, which are identified as digital rights and given value exclusively in digital form. Digital rights and freedoms are integrated in the conditions of the transition to the digital development of innovative business.
Keywords: innovative entrepreneurship; business; criteria; identification; intellectual assets; innovativeness; controllability; economy; digital transformation